The good lawyer : seeking quality in the practice of law - Linder, Douglas O.
"Doug Linder and Nancy Levit combine evidence from the latest social science research with numerous engaging accounts of able attorneys at work to explain just what makes a good lawyer -- courage, empathy, integrity, realism, a strong sense of justice, clarity of purpose, and an ability to transcend emotionalism"--